Evaluation of Primary Service Readiness in Handling Catastrophic Disease Emergencies in Rural Areas - Syahputra, Tengku Muhammad Reza (JURNAL PENGMAS KESTRA (JPK), 2024)
Catastrophic illnesses, such as stroke, heart attack, and serious accidents, are medical conditions that require rapid and appropriate treatment to prevent death or disability. In rural areas, access to health services is often limited, and the readiness of primary care services in handling catastrophic emergencies is very important. Evaluation of the readiness of primary care facilities is needed to determine how effective these services are in dealing with urgent medical events. This study aims to evaluate the readiness of primary care services in handling catastrophic emergencies in rural areas. Specifically, this study aims to determine the facilities, resources, and skills of medical personnel available in handling emergency cases. This study uses a quantitative design with an observational analytical approach. Data were collected through surveys and interviews with related parties at primary care facilities in rural areas. Univariate analysis was conducted to describe the frequency distribution of variables related to service readiness, while bivariate analysis used the chi-square test to determine the relationship between certain factors (such as facilities, medical personnel training, and community readiness) with the ability of primary care services to handle catastrophic emergencies. The results of univariate analysis showed that most primary care services in rural areas do not have complete facilities to handle catastrophic diseases. Only 40% of facilities have basic equipment such as defibrillators and heart monitors, while 60% do not have adequate equipment. In terms of human resources, 50% of medical personnel in rural areas have not received special training to handle medical emergencies, and only 30% have training in handling catastrophic diseases. Bivariate analysis showed a significant relationship between medical personnel training and the success of emergency management, with better results in facilities with trained medical personnel (p < 0.05). In addition, the readiness of the community to seek immediate medical help also had a significant effect on the success of treatment (p < 0.05)